Incidencia de la evaluación formativa en el proceso de aprendizaje de los niños del quinto año de educación general básica paralelo “A” de la Escuela de Educación Básica Luis Felipe Borja de la parroquia de Toacaso cantón Latacunga provincia Cotopaxi durante el periodo 2014-2015 - Defaz Chicaiza, Nancy Marisol (2015)
In the present research work it has focused on guiding the training workshop for school teachers Luis Felipe Borja by exposing thematic formative evaluation to solve the weak implementation of this evaluation in the process of learning of Students of the aforementioned institution. In this context theoretical aspects were considered from concepts, functions, methods, techniques and resources. For the realization of the proposal it was considered necessary to conduct a field investigation in which techniques are used as the survey and interview took into account the needs of teachers Institution Luis Felipe Borja, from this perspective that the training met It should be conducted with all teachers being directly participate in the learning of children. Finely implementation of formative assessment workshops strengthened the teachers know the importance of this evaluation the process of learning of children / as the institution.